Environment, Policies, and Addictions to Social Networks Among University Students: Entorno y políticas en relación a las adicciones a las redes sociales entre universitarios | 环境、政策与大学生社交网络成瘾 - Valdez Roca, Alvaro Fernando (2024)
The two main topics were essentially addressed. Firstly, and of great concern in the university setting, is related to addictive behaviors in the use of social media by students. Secondly, less explored in the country, is the various policies being implemented to address this phenomenon.